PEMIKIRAN EKONOMI IBNU TAIMIYAH - Fasiha Fasiha (Al-Amwal : Journal of Islamic Economic Law, 2017)
The development of Islamic economics can not be separated from the historical development of Islamic civilization. The study of the history of economic thought by analyzing the description of economic thinking Ibn Taymiyyah and the history of life that affect the economic thinking of Ibn Taymiyyah. According to Ibn Taymiyyah pricing by the government is good, but not absolute, because the actual prices are set by the forces of demand and supply. Another case, if the price increases caused by injustice market mechanism, the government may intervene in pricing. To achieve this purpose, it is necessary formation hisbah institutions with the aim of protecting the interests of buyers and sellers